Toolbox for in vivo imaging of host-parasite interactions at multiple scales - Niz, Mariana De; Frischknecht, Friedrich (Trends in parasitology, 2019)
Animal models have for long been pivotal for parasitology research. Over the last few years, techniques such as intravital, optoacoustic and magnetic resonance imaging, optical projection tomography, and selective plane illumination microscopy developed promising potential for gaining insights into host-pathogen interactions by allowing different visualization forms in vivo and ex vivo. Advances including increased resolution, penetration depth, and acquisition speed, together with more complex image analysis methods, facilitate tackling biological problems previously impossible to study and/or quantify. Here we discuss advances and challenges in the in vivo imaging toolbox, which hold promising potential for the field of parasitology.
Gesehen am 04.09.2019